2017
DOI: 10.1016/j.jvir.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Low-Flow Vascular Malformations of the Extremities Using MR-Guided High Intensity Focused Ultrasound: Preliminary Experience

Abstract: Five patients with painful vascular malformations of the extremities that were refractory to standard treatment and that were confirmed as low flow using dynamic contrast-enhanced MRI were treated with magnetic resonance imaging guided high intensity focused ultrasound (MRgFUS). Daily pain scores improved (max, pre = 8.4±1.5; post = 1.6±2.2, P = 0.004) at median follow up of 9 months (range 4 – 36 months). The size of vascular malformations decreased on follow-up MR imaging (enhancing volume, 8.2 mL [0.7–10.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Ghanouni et al [ 12 ] presented results of MR-HIFU treatments of four patients with vascular malformations. The vascular malformations were located in the thigh or calf at an average focal depth of 14.9 cm.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghanouni et al [ 12 ] presented results of MR-HIFU treatments of four patients with vascular malformations. The vascular malformations were located in the thigh or calf at an average focal depth of 14.9 cm.…”
Section: Case Presentationmentioning
confidence: 99%
“…Ghanouni et al [ 12 ] from Stanford University presented results of MR-HIFU ablation of slow-flow vascular malformations obtained in four patients during the 15th International Symposium of Therapeutic Ultrasound 2015 in Utrecht, The Netherlands. The average ratio of the non-perfused volume to the total tumor volume was 2.6 (range 0.75–7.4).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to applications in functional neurosurgery and neuro-oncology (5, 6) HIFU for intracranial vascular lesions is less studied and no investigation of brain AVM has been published. However, data from peripheral vascular ablation by focused ultrasound in both animal models and man is encouraging (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Other work demonstrated that MRgFUS can effectively treat vascular malformations, with one study showing a statistically significant pain reduction (8.4 ± 1.5 to 1.6 ± 2.2; p = 0.004) and decreased tumor volume in five patients. 60…”
Section: Other Indicationsmentioning
confidence: 99%